2012
DOI: 10.7150/ijms.4895
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Digital Cervicography and Pathological Diagnosis Performed at Private Clinics in Korea

Abstract: Objective: To evaluate the correlation tendency between abnormal findings of digital cervicography and cervical pathology at private clinics in Korea.Methods: Abnormal finding of digital cervicography performed at private clinics in Korea between January 1, 2010 and May 31, 2012 were analysed retrospectively. The patient's age, abnormal findings of digital cervicography, cervical cytology, human papillomaviru (HPV) test and cervical pathology were investigated and the rate of agreement between abnormal finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In 2012, Bae et al, (2012) assessed the utility of a 35mm camera to record cervical images. In this retrospective study, agreement rates between cervicography and pathology in CIN I, CIN II or III, and cervical cancer were 52.0%, 78.9%, and 90.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, Bae et al, (2012) assessed the utility of a 35mm camera to record cervical images. In this retrospective study, agreement rates between cervicography and pathology in CIN I, CIN II or III, and cervical cancer were 52.0%, 78.9%, and 90.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This method is known as digital cervicography and consists of provision of VIA followed by an additional step whereby a digital camera is used to transmit a photographic image of the cervix to a television screen or computer monitor that can be reviewed at higher clarity and resolution than is available with the naked eye. 13 , 14 This method has been in use in Zambia since 2006, with well-established programs to improve nurse training in CCS and treatment. 8 , 15 The Zambian program has incorporated Internet transfer of digital cervical photographic images for review and mentorship by experts at a coordinating site.…”
Section: Introductionmentioning
confidence: 99%
“…Bae et at. [ 4 ] also found that there were high concordance rate between abnormal findings of digital cervicography and final precancerous lesions. However, above studies did not compared the DCSs with conventional film cervicography.…”
Section: Discussionmentioning
confidence: 97%